Expert System for Diagnosing Hepatitis Disease Using the Forward Chaining Method - Yessi Mardiana; Devina Nino Sari; Nofi Qurniati (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Hepatitis is a liver disease characterized by inflammation. Inflammation is indicated by elevated liver enzyme levels, which are caused by disruption or damage to the liver membrane. Given the significant negative impact of this disease, serious prevention and treatment of the dangers of hepatitis are necessary. Efforts to minimize these risks can be achieved by increasing public awareness of the factors that can cause hepatitis. Therefore, a system is needed that can serve as an alternative to consulting a doctor for the general public. The purpose of this research is to develop an expert system that can serve as an initial solution in the treatment of hepatitis. In its implementation, this expert system uses the forward chaining method. In this method, data is used to determine which rules will be executed to achieve a result. Based on the testing conducted, it can be concluded that this expert system application can be used by users for the early diagnosis of hepatitis